2007
DOI: 10.1159/000109224
|View full text |Cite
|
Sign up to set email alerts
|

Gamma 2 Actin Gene (Enteric Type) Polymorphism Is Not Associated with Obstetric Cholestasis or Preeclampsia

Abstract: Objective: To determine whether genetic variability in the intron 1 region of the gamma 2 actin gene (enteric type) contributes to the development of obstetric complications. Study Design: The study involved 57 obstetric cholestasis and 133 preeclampsia patients and a control group of 115 healthy women in whom polymerase chain reaction detection of insertion-deletion polymorphism in the gamma 2 actin gene was investigated. χ2 analysis was used to assess genotype and allele frequency differences betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 62 publications
0
1
0
Order By: Relevance
“…As previously reported, FOXP3 [446], TIMP4 [447], OAS3 [448], SOCS1 [128], CD74 [129], PLK1 [449], TGFB1 [450], RAPGEF1 [451], SERPINH1 [452], ATF5 [66], GATA6 [133], IGF2BP1 [453], IRX3 [454], FOXC2 [455], SNHG17 [456], TAF1C [457], HHIP (hedgehog interacting protein) [458], POMC (proopiomelanocortin) [459], DOK5 [76], COL1A1 [460], POSTN (periostin) [461], SOD3 [462], ADAMTS13 [463], FABP5 [464], MAPK11 [465], KCTD15 [83], HSPG2 [466], MST1 [467], MGAT2 [468], LGR5 [469], SPINK1 [470], CYP19A1 [471], PLAC8 [90], CD36 [472], AQP5 [473], GIPR (gastric inhibitory polypeptide receptor) [474], ARG1 [475], SORL1 [476], CD4 [477], F11R [478], LEPR (leptin receptor) [479], CDH13 [480], AR (androgen receptor) [481], FOXO1 [102], MALT1 [482], PAM (peptidylglycine alpha-amidating monooxygenase) [483], B2M [484], TCF4 [485], CAV2 [486], HSBP1 [487], COLEC12 [488], ADRA2A [489], SLC38A4 [490], TM6SF2 [491], GLP2R [111], KLB (klotho beta) [492], NFAT5 [493], PON2 [494], ZMAT3 [495], DST (dystonin) [426], MGST3 [496], COQ2 [118], EPHX2 [497], C2 [181] and FAM3C [120] are altered expression in type 2 diabetes mellitus. Previous studies have shown that DRD4 [498], TIMP4 [499], SOCS1 [500], CD74 [501], TGFB1 [502], ACTG2 [503], ISG15 [504], HOXC8 [505], SNHG17 [506], IL1RL1 […”
Section: Discussionmentioning
confidence: 99%
“…As previously reported, FOXP3 [446], TIMP4 [447], OAS3 [448], SOCS1 [128], CD74 [129], PLK1 [449], TGFB1 [450], RAPGEF1 [451], SERPINH1 [452], ATF5 [66], GATA6 [133], IGF2BP1 [453], IRX3 [454], FOXC2 [455], SNHG17 [456], TAF1C [457], HHIP (hedgehog interacting protein) [458], POMC (proopiomelanocortin) [459], DOK5 [76], COL1A1 [460], POSTN (periostin) [461], SOD3 [462], ADAMTS13 [463], FABP5 [464], MAPK11 [465], KCTD15 [83], HSPG2 [466], MST1 [467], MGAT2 [468], LGR5 [469], SPINK1 [470], CYP19A1 [471], PLAC8 [90], CD36 [472], AQP5 [473], GIPR (gastric inhibitory polypeptide receptor) [474], ARG1 [475], SORL1 [476], CD4 [477], F11R [478], LEPR (leptin receptor) [479], CDH13 [480], AR (androgen receptor) [481], FOXO1 [102], MALT1 [482], PAM (peptidylglycine alpha-amidating monooxygenase) [483], B2M [484], TCF4 [485], CAV2 [486], HSBP1 [487], COLEC12 [488], ADRA2A [489], SLC38A4 [490], TM6SF2 [491], GLP2R [111], KLB (klotho beta) [492], NFAT5 [493], PON2 [494], ZMAT3 [495], DST (dystonin) [426], MGST3 [496], COQ2 [118], EPHX2 [497], C2 [181] and FAM3C [120] are altered expression in type 2 diabetes mellitus. Previous studies have shown that DRD4 [498], TIMP4 [499], SOCS1 [500], CD74 [501], TGFB1 [502], ACTG2 [503], ISG15 [504], HOXC8 [505], SNHG17 [506], IL1RL1 […”
Section: Discussionmentioning
confidence: 99%